Nitric oxide-mediated the therapeutic properties of induced pluripotent stem cell for paraquat-induced acute lung injury - Cui, Anfeng; Li, Shirui; Li, Yijun; Yang, Dawei; Huang, Jiongwei; Wang, Xuemeng; Song, Nana; Chen, Fuchen; Chen, Sifeng; Xiang, Meng (Frontiers in Immunology, 2023)
The mortality rate associated with acute lung injury (ALI) and its severe form, acute respiratory distress syndrome, is high. Induced pluripotent stem cell (iPSC) therapy is a potential treatment method for ALI, but its therapeutic efficacy is limited in injured lungs. Nitric oxide (NO) has various physiological actions. The current study investigated the effect of iPSCs pretreated with NO donors in paraquat (PQ)-induced ALI mouse model. Male C57BL/6 mice were intraperitoneally injected with PQ, followed by infusion of phosphate-buffered saline, iPSCs, L-arginine pretreated iPSCs, or Nitro-L-arginine methylester (L-NAME) pretreated iPSCs through the tail veins. Histopathological changes, pulmonary microvascular permeability, and inflammatory cytokine levels were analyzed after 3 or 28 d. The effects on iPSC proliferation, migration, and adhesion were evaluated in vitro. More L-arginine-pretreated iPSCs were selectively trafficked into the injured pulmonary tissue of mice with LPS-induced ALI, drastically diminishing the histopathologic changes and inflammatory cytokine levels (IL-1β and IL-6). There was also markedly improved pulmonary microvascular permeability and pulmonary function. The NO inhibitor abolished the protective effects of iPSCs. In addition, the ability of L-arginine to promote the proliferation and migration of iPSCs was decreased by L-NAME pretreatment, suggesting that NO might mediate the therapeutic benefits of iPSC. The improvement of the iPSC physiological changes by the endogenous gaseous molecule NO reduces lung injury severity. L-Arginine represents a pharmacologically important strategy for enhancing the therapeutic potential of iPSCs.